2009
DOI: 10.1111/j.1600-0560.2008.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial light microscopy of experimental phytophotodermatitis in animal model

Abstract: PPD can be successfully reproduced in rat skin. After 24 h spongiosis, vacuolization and keratinocyte necrosis are observed, clinically there are no changes. After 48 h, erythema appears with intra- and subepidermal blistering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…[7] reproduce phytophotodermatitis in animal models by spraying peel juice of Tahiti lemon onto the skin of epilated albino rats and observe its serial pathological changes. After 24 h spongiosis, vacuolization and keratinocyte necrosis are observed, clinically there are no changes.…”
Section: Discussionmentioning
confidence: 99%
“…[7] reproduce phytophotodermatitis in animal models by spraying peel juice of Tahiti lemon onto the skin of epilated albino rats and observe its serial pathological changes. After 24 h spongiosis, vacuolization and keratinocyte necrosis are observed, clinically there are no changes.…”
Section: Discussionmentioning
confidence: 99%
“…Phototoxicity and photosensitization studies are presented in Table 12. 25,28,[38][39][40][41][42] No photo irritation was observed in an in vitro study of Citrus Reticulata (Tangerine) Peel Extract (3.0% in formulation). Citrus Auratnium Amara (Bitter Orange) Peel Extract (2.0% in formulation) did not induce photo irritation or photosensitization in guinea pigs.…”
Section: Phototoxicity and Photosensitizationmentioning
confidence: 99%
“…Animal models are used in experimental studies on phototoxic dermatoses [36][37][38][39][40] , including PPD [41][42][43] , which could be successfully reproduced in rats. PPD was reproduced in the experimental model using only the lemon peel juice, in accordance the results obtained with the experimental studies on humans [32] and consistent with the findings of another study, in which the psoralens in the lemon peel were found in concentrations 13 to 182 higher than in the fruit juice [44] .…”
Section: Discussionmentioning
confidence: 99%
“…The light microscopy revealed an epithelial lesion that appeared in 24 hours, however, the erythema was only clinically evident on the dorsum of the animals after 48 hours ( Figure 4). In a another study, with exposure times ranging from 5 to 8 min, a serial histological study on the epidermal changes immediately after induction was performed: after 1, 2, 4, 6, 24, 48 and 72 h, the left half of each rat was used as the control and was only exposed to sunlight; in another area only peel lemon juice was applied [42] .…”
Section: E X P E R I M E N T a L S T U D I E S O N P P D Reproductionmentioning
confidence: 99%